Results of a phase I/IIa trial of SV-BR-1-GM inoculation with low-dose cyclophosphamide and interferon alpha (Bria-IMT) in metastatic breast cancer - Charles L. Wiseman; Jarrod P. Holmes; Carmen Calfa; Shaker R. Dakhil; Saveri Bhattacharya; George E. Peoples; Markus D. Lacher; Miguel Lopez-Lago; Alex Kharazi; Giuseppe Del Priore; Mingjin Chang; Daniel L. Adams; et al. (Human Vaccines & Immunotherapeutics)
This Phase I/IIa open-label, single-arm clinical trial addressing advanced, refractory, metastatic breast cancer was conducted at six medical centers in the United States. We repeated inoculations with irradiated SV-BR-1-GM, a breast cancer cell line with antigen-presenting activity engineered to release granulocyte-macrophage colony-stimulating factor (GM-CSF), with pre-dose low-dose cyclophosphamide and post-dose local interferon alpha. Twenty-six patients were enrolled; 23 (88.5%) were inoculated, receiving a total of 79 inoculations. There were six Grade 4 and one Grade 5 adverse events noted (judged unrelated to SV-BR-1-GM). Disease control (stable disease [SD]) occurred in 8 of 16 evaluable patients; 4 showed objective regression of metastases, including 1 patient with near-complete regressions in 20 of 20 pulmonary lesions. All patients with regressions had human leukocyte antigen (HLA) matches with SV-BR-1-GM; non-responders were equally divided between matching and nonmatching (p = .01, Chi-squared), and having ≥2 HLA matches with SV-BR-1-GM (n = 6) correlated with clinical benefit. Delayed-type hypersensitivity (DTH) testing to candida antigen and SV-BR-1-GM generated positive responses (≥5 mm) in 11 (42.3%) and 13 (50%) patients, respectively. Quantifying peripheral circulating tumor cells (CTCs) and cancer-associated macrophage-like cells (CAMLs) showed that a drop in CAMLs was significantly correlated with an improvement in progression-free survival (PFS; 4.1 months vs. 1.8 months, p = .0058). Eight of 10 patients significantly upregulated programmed cell death ligand 1 (PD-L1) on CTCs/CAMLs with treatment (p = .0012). These observations support the safety of the Bria-IMT regimen, demonstrate clinical regressions, imply a role for HLA matching, and identify a possible value for monitoring CAMLs in peripheral blood.